ChemInform Abstract: Exceptionally E‐ and β‐Selective NHC—Cu‐Catalyzed Proto‐Silyl Additions to Terminal Alkynes and Site‐ and Enantioselective Proto‐Boryl Additions to the Resulting Vinylsilanes: Synthesis of Enantiomerically Enriched Vicinal and Geminal Borosilanes. Issue 30 (4th July 2013) - Meng, Fanke; Jang, Hwanjong; Hoveyda, Amir H.
Abstract Protosilylation of aliphatic and aromatic terminal alkynes proceeds with complete (E)‐β‐selectivity.